2009
DOI: 10.1017/s0022112009991509
|View full text |Cite
|
Sign up to set email alerts
|

Steep capillary-gravity waves in oscillatory shear-driven flows

Abstract: We study steep capillary-gravity waves that form at the interface between two stably stratified layers of immiscible liquids in a horizontally oscillating vessel. The oscillatory nature of the external forcing prevents the waves from overturning, and thus enables the development of steep waves at large forcing. They arise through a supercritical pitchfork bifurcation, characterized by the square root dependence of the height of the wave on the excess vibrational Froude number (W , square root of the ratio of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 29 publications
5
30
0
Order By: Relevance
“…It is worth highlighting that it is the first experimental evidence of spatially modulated waves on an interface caused by horizontal vibrations. Previous experimental studies of wave patterns under horizontal vibrations with immiscible fluids (Jalikop & Juel 2009;Yoshikawa & Wesfreid 2011b;Gandikota et al 2014b) did not report wave modulation, although it was theoretically predicted by Varas & Vega (2007) in a nearly inviscid fluid subjected to horizontal vibration. We will return to this pattern in § 4.3.…”
Section: Dynamics Of An Interface Near the Onset Of Instabilitymentioning
confidence: 92%
See 2 more Smart Citations
“…It is worth highlighting that it is the first experimental evidence of spatially modulated waves on an interface caused by horizontal vibrations. Previous experimental studies of wave patterns under horizontal vibrations with immiscible fluids (Jalikop & Juel 2009;Yoshikawa & Wesfreid 2011b;Gandikota et al 2014b) did not report wave modulation, although it was theoretically predicted by Varas & Vega (2007) in a nearly inviscid fluid subjected to horizontal vibration. We will return to this pattern in § 4.3.…”
Section: Dynamics Of An Interface Near the Onset Of Instabilitymentioning
confidence: 92%
“…The effect of horizontal vibrations on two superposed immiscible liquids has been examined both experimentally (Wolf 1969(Wolf , 1970Ivanova, Kozlov & Evesque 2001;Talib, Jalikop & Juel 2007;Mialdun et al 2008;Jalikop & Juel 2009;Yoshikawa & Wesfreid 2011b) and theoretically (Lyubimov & Cherepanov 1987;Khenner et al 1999), where it was shown that if the state of the flat contact line is unstable, nonpropagating periodic waves may occur on the interface. Following Wunenburger et al (1999), these waves, which are stationary in the reference frame of the vibrated cell, are referred to as 'frozen waves'.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Only the tips of the oil fingers oscillate with a small amplitude. Jalikop & Juel (2009) investigated saturated waves generated in oscillatory two-layer flows, by experiments in a horizontally vibrated parallelepiped container. The considered upper-layer fluids were silicone oils of viscosities 114 mm 2 /s and 210 mm 2 /s.…”
Section: Wave Evolutionmentioning
confidence: 99%
“…The behaviour of an interface of immiscible liquids under horizontal vibrations in a container with end walls demonstrates the emergence of spatially periodic waves on the interface, which are often referred to as 'frozen waves' (Lyubimov & Cherepanov 410 V. Shevtsova and others 1987;Khenner et al 1999;Ivanova, Kozlov & Evesque 2001;Jalikop & Juel 2009;Gandikota et al 2014). The frozen waves are caused by a shear driven mechanism similar to the Kelvin-Helmholtz instability.…”
Section: Introductionmentioning
confidence: 99%